Logo Creation Algorithm - Radovan Madlenak; Lucia Madlenakova; Jana Strbova; Jozef Stefunko (Communications - Scientific letters of the University of Zilina, 2014)
This article is dedicated to corporate design and its impact on online users. It contains definitions of basic concepts and terms of corporate identity. Particular attention is then paid to corporate design and its features – name of the company, slogan, logo, corporate colors, typography, mascot and signature tune. In the main part of article we present the algorithm which should help small and starting online companies to create their own logo without help of professional designers.